Assessing competencies of trainee sport psychologists: An examination of the 'structured case presentation' assessment method. (March 2016) - Hutter, R.I. (Vana); Pijpers, J.R. (Rob); Oudejans, Raôul R.D.
Abstract: Objectives: There is virtually no literature on how to assess competencies of applied sport psychologists. We assessed casework of applied sport psychology students and compared written case report assessment (WCRA) with structured case presentation assessment (SCPA) on reliability and acceptability (e.g., validity, transparency, feedback function and preference of methods, as perceived by students and assessors). Design: A quantitative, comparative study of two assessment methods. Method: Participants were 11 students, nine supervisors and three exam committee members. A number of 18 cases were evaluated with both WCRA by the supervisor and SCPA by two exam committee members. Ten of these cases were also evaluated with WCRA by exam committee members. Interrater reliability measures were calculated and compared for the different assessment methods. Participants' perception of the validity, transparency, and feedback function of the methods, and the preferences for assessment methods were surveyed with a brief questionnaire. Results: SCPA by the exam committee resulted in higher interrater reliability than WCRA by supervisor and exam committee. The feedback function of SCPA seemed superior to WCRA by either supervisor or exam committee. For assessment by the exam committee, the perceived validity and transparency of SCPA seemed higher than of WCRA. Students and exam committee had the highest preference for SCPA by supervisor and exam committee. Conclusions: Overall it can be concluded that, for assessment by the exam committee, structured case presentations provided a more reliable and acceptable method of assessment than written case reports only. Highlights: Two methods of assessing casework were compared on reliability and acceptability. SCPA resulted in higher inter-rater reliability than WCRA. Students and exam committee prefer SCPA by supervisor and exam committee. For assessment by the exam committee SCPA provide a more reliable and acceptable method than WCRA.